Prophylactic and therapeutic vaccine against Pseudomonas aeruginosa keratitis using bacterial membrane vesicles. Issue 23 (27th May 2021) - Ito, Saori; Nakamura, Jutaro; Fukuta, Michiko; Ura, Takehiro; Teshigawara, Takeshi; Fukushima, Jun; Mizuki, Nobuhisa; Okuda, Kenji; Shimada, Masaru
Abstract: Purpose: Pseudomonas aeruginosa ( P. aeruginosa ) infection is one of the major causes of keratitis. However, effective prophylactic and therapeutic vaccines against P. aeruginosa keratitis have yet to be developed. In this study, we explored the use of P. aeruginosa membrane vesicles (MVs) as a prophylactic vaccine as well as the use of immune sera derived from P. aeruginosa MV-immunized animals as a treatment for P. aeruginosa corneal infections in C57BL/6 mice. Methods: C57BL/6 mice were intramuscularly immunized with P. aeruginosa MVs; the mouse corneas were then scarified and topically infected with several P. aeruginosa strains, followed by determination of corneal clinical score and corneal bacterial load. Next, immune sera derived from P. aeruginosa MV-immunized ICR mice were administered intraperitoneally to naïve C57BL/6 mice, followed by topical P. aeruginosa challenge. Finally, the immune sera were also used as a topical treatment in the mice with established P. aeruginosa corneal infections. Results: P. aeruginosa -specific IgG and IgA antibodies induced by intramuscular immunization were detected not only in the sera but also in the eye-wash solution. Both active and passive immunization significantly inhibited P. aeruginosa corneal infection. Finally, topical treatment with immune sera in the mice with established P. aeruginosa corneal infections notably decreased the corneal clinical score and corneal bacterial load. Conclusions: P. aeruginosa keratitis can be attenuated by vaccination of P. aeruginosa MVs and topical application of P. aeruginosa MV-specific immune sera.